Bringing fossils to life : An introduction paleobiology - Prothero, Donald R (New York : Columbia, 2013)
One of the leading textbooks in its field, Bringing Fossils to Life applies paleobiological principles to the fossil record while detailing the evolutionary history of major plant and animal phyla. It incorporates current research from biology, ecology, and population genetics, bridging the gap between purely theoretical paleobiological textbooks and those that describe only invertebrate paleobiology and that emphasize cataloguing live organisms instead of dead objects. For this third edition Donald R. Prothero has revised the art and research throughout, expanding the coverage of invertebrates and adding a discussion of new methodologies and a chapter on the origin and early evolution of life.
Glossary 607-618p.; Bibliography 619-656p.; Index 657-671p.
Keywords: Extinction; Spiny skins; Variation in fossils